Comparisons of the tolerability and sensitivity of quetiapine-XR in the acute treatment of schizophrenia, bipolar mania, bipolar depression, major depressive disorder, and generalized anxiety disorder - Wang, Zuowei (2010)
Quetiapine extended-release (quetiapine-XR) has been studied in patients with schizophrenia, bipolar mania, bipolar depression, major depressive disorder (MDD), and generalized anxiety disorder (GAD). The purpose of this study was to compare the tolerability and sensitivity of quetiapine-XR among these psychiatric conditions. The discontinuation due to adverse events (DAEs) and reported somnolence in randomized, double-blind, placebo-controlled studies of quetiapine-XR in these psychiatric conditions were examined. The absolute risk reduction or increase and the number needed to treat to benefit (NNTB) or harm (NNTH) for DAEs and reported somnolence of quetiapine-XR ≥300 mg/d relative to placebo were estimated. Data from one study in schizophrenia (n=465), one in mania (n=316), one in bipolar depression (n=280), two in refractory MDD (n=624), two in MDD (n=669) and three in GAD (n=1109) were available. The risk for DAEs of quetiapine-XR relative to placebo was significantly increased in bipolar depression (NNTH=9), refractory MDD (NNTH=8), MDD (NNTH=9), and GAD (NNTH=5), but not in schizophrenia and mania. The risk for reported somnolence of quetiapine-XR relative to placebo was significantly increased in schizophrenia (600 mg/d NNTH=15 and 800 mg/d NNTH=11), mania (NNTH=8), bipolar depression (NNTH=4), refractory MDD (NNTH=5), MDD (NNTH=5) and GAD (NNTH=5). These results suggest that patients with GAD had the poorest tolerability during treatment with quetiapine-XR, but they had a similar sensitivity as those with bipolar depression and MDD. Patients with schizophrenia or mania had a higher tolerability and a lower sensitivity than those with bipolar depression, MDD, or GAD.